Manajemen SDM dalam kaitannya dengan upaya peningkatan mutu pendidikan di SMA Negeri 3 Magelang tahun pelajaran 2013/2014 - Sugeng Haryanto; Supriyoko Supriyoko (Universitas Sarjanawiyata Tamansiswa, 2016)
The object of research is to know and discuss deeper about 1) the implementation of human resource management at SMA Negeri 3 Magelang. 2) the Effectiveness of management for human resource inÂ SMA Negeri 3 Magelang in increasing of school quality. 3) the factors that support and obstruct the management of human resource in increasing the school quality at SMA Negeri 3 Magelang. The research is a descriptive-analytical nonstatistical research by using the qualitative approach and case study. Â The collecting data is through on observation, which the researcher functioned as an instrument for making on observation nonparticipant, deep interview and primer data resource and documentation study. The data is analyzed by using interactive analysis through 3 activities that are a reduction, display, and concluding. The validity of data is obtained through prolongation of participant and triangulation data. Based on the research is described that The result of the research data can be described that the management of SMA Negeri 3 Magelang human resource in general based on the deep observation and interview result supported with the document study has been very good. The effectiveness of human resource management in SMA Negeri 3 Magelang in terms of its efforts to improve the quality seen from the internal customer satisfaction perspective of teacher and staff, as matter of fact, it can be categorized as good, although this category has not fully touched all aspects of the satisfaction, especially aspects of physical development. Factors supporting the human resource management in SMA Negeri 3 Magelang in improving the quality of education: First, the school's vision that tries to do â€œ Prestige Workâ€. Second, the school leadership is democratic, participatory. Third, the human resource which always undergoes the improvement of the capability. Fourth, adequate available facilities support every activity. And fifth, a conducive culture that encourages the school community to keep improving their quality and ability. Factor-factors that can inhibit the human resource management in SMA Negeri 3 Magelang in the effort of improving the quality of education are: First, the welfare that still needs attention, especially for the teachers and staffs who are still private. Second, the clarity of career needs to be concerned, if this does not endeavor, it is worried it will also be able to influence and disturb the totality of their professional work. Third, the quality is not optimal qualified and valid communication in his socialization.